Tumor-associated macrophages and the profile of inflammatory cytokines in oral squamous cell carcinoma - Costa, Nadia Lago; Valadares, Marize Campos; Souza, Pedro Paulo Chaves [UNESP]; Mendonça, Elismauro Francisco; Oliveira, José Carlos; Silva, Tarcíla Aparecida; Batista, Aline Carvalho (Elsevier, 2013)
Objective: To evaluate and characterize macrophage populations (M1/M2) in the tumor microenvironment of oral cavity squamous cell carcinoma (OCSCC). The relationship between macrophages and clinicopathological factors, such as survival data, lymph node metastasis, tumoral proliferation, and WHO histological grading are also analyzed. Materials and methods: The samples consisted of surgically excised specimens from patients with non-metastatic and metastatic OCSCC and normal oral mucosa (control). Immunohistochemistry, flow cytometry, and qRT-PCR were used to evaluate macrophage populations and the expression of pro- (IL-12, IL-23, and INF-γ) and anti-inflammatory (IL-10 and TGF-β) cytokines. The level required for statistical significance was defined as p < 0.05. Results: The data showed a predominance of M2 phenotype (high percentage of IL-10+TGF-β+) macrophages in the tumor microenvironment of OCSCC. A higher percentage of macrophages expressing TGF-β was seen in the OCSCC group when compared with healthy individuals. The assessment of mRNA expression also presented a greater expression of anti-inflammatory cytokines TGFβ and IL10 in OCSCC when compared with the control group. The percentage of macrophages, demonstrated by immunohistochemistry, was significantly higher in the metastatic OCSCC group than in the non-metastatic and control groups. The log-rank test also showed that the mean survival time for patients with high levels of macrophages was less (44 months) when compared with patients with a low percentage of such cells (93 months). Conclusion: A predominance of the M2 phenotype in the tumor microenvironment of OCSCC could contribute to local immunosuppression, via TGF-β production, and consequently greater lymph node involvement and reduced patient survival time. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Cytokines; Interferon-gamma; Interleukin-10; Interleukin-12; Interleukin-23; Macrophages; Oral cancer; Squamous cell carcinoma; Transforming growth factor beta; gamma interferon; interleukin 10; interleukin 12; interleukin 23; messenger RNA; transforming growth factor beta; adult; aged; cancer invasion; cancer staging; cancer survival; cell population; cell proliferation; controlled study; cytokine release; female; flow cytometry; histopathology; human; human cell; human tissue; immunohistochemistry; lymph node metastasis; macrophage; major clinical study; male; mouth mucosa; mouth squamous cell carcinoma; nucleotide sequence; phenotype; priority journal; retrospective study; reverse transcription polymerase chain reaction; survival time; tumor associated leukocyte; tumor localization; tumor microenvironment; tumor volume; Adult; Aged; Aged, 80 and over; Antigens, CD11; Carcinoma, Squamous Cell; Cell Count; Cell Proliferation; Female; Follow-Up Studies; Humans; Immune Tolerance; Inflammation Mediators; Lymphatic Metastasis; Male; Middle Aged; Mouth Neoplasms; Neoplasm Grading; Neoplasm Invasiveness; Retrospective Studies; Survival Rate; Transforming Growth Factor beta; Tumor Microenvironment